A New Category of Death: Medical Assistance in Dying and Mental Illness in Canada - Badone, Ellen (Anthropologica, 2025)
Since June 2016, federal law in Canada has permitted eligible adults to request medical assistance in dying (MAiD). Until March 2021, however, the law stipulated that only those whose natural death was “reasonably foreseeable” were eligible to access MAiD. At that time, the legislation was changed to permit MAiD for anyone with a “grievous and irremediable medical condition,” including mental illness. For the latter category, however, a series of delays in enacting the legislation has postponed it until March 2027. Using publicly available sources, including testimony at Senate hearings on this issue, this paper explores debates among psychiatrists on the issue of extending MAiD to those suffering solely from mental illness. While some psychiatrists claim that the denial of MAiD for grievous and irremediable mental illness is paternalistic and discriminates against the mentally ill, others argue that there is a lack of scientific evidence to support the idea that any mental illness is irremediable and that high-quality mental healthcare can alleviate suffering, making MAiD unnecessary. Still others point to the vulnerability of people with mental illness and their potential lack of capacity for decision-making, as well as to inequities in access to mental healthcare despite Canada’s publicly funded healthcare system. This paper analyzes these competing discourses and argues that one stems from an ethical stance of reasoning from first principles, while the other is based on a feminist ethic of care. Additionally, I suggest that the arguments against MAiD for grievous and irremediable mental illness are rooted in Cartesian dualism, which posits a clear distinction between mind and body. Ultimately, I conclude that MAiD, as a new conceptual category of death, remains in a liminal state, and that the debates over MAiD in Canada also reflect debates about the nature of embodied life.